Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure, let's analyze how to transform the given quartic function [tex]\( f(x) = x^4 \)[/tex] by translating it 3 units to the right and 1 unit down.
### Step 1: Translation 3 Units to the Right
To translate the function [tex]\( f(x) = x^4 \)[/tex] 3 units to the right, we replace [tex]\( x \)[/tex] with [tex]\( x - 3 \)[/tex]. This gives us the new function:
[tex]\[ g(x) = (x - 3)^4 \][/tex]
### Step 2: Translation 1 Unit Down
Next, we translate the function [tex]\( g(x) = (x - 3)^4 \)[/tex] 1 unit down. To do this, we subtract 1 from the entire function:
[tex]\[ g(x) = (x - 3)^4 - 1 \][/tex]
Thus, the equation that represents the transformation of the parent quartic function [tex]\( f(x) = x^4 \)[/tex] by translating it 3 units to the right and 1 unit down is:
[tex]\[ g(x) = (x - 3)^4 - 1 \][/tex]
### Conclusion
From the given options:
A. [tex]\( g(x) = (x - 3)^4 - 1 \)[/tex]
B. [tex]\( g(x) = (x - 1)^4 + 3 \)[/tex]
C. [tex]\( g(x) = (x + 3)^4 - 1 \)[/tex]
D. [tex]\( g(x) = (x + 1)^4 + 3 \)[/tex]
Option A, [tex]\( g(x)=(x-3)^4-1 \)[/tex], correctly represents the transformation. Therefore, the correct answer is:
[tex]\[ \boxed{A} \][/tex]
### Step 1: Translation 3 Units to the Right
To translate the function [tex]\( f(x) = x^4 \)[/tex] 3 units to the right, we replace [tex]\( x \)[/tex] with [tex]\( x - 3 \)[/tex]. This gives us the new function:
[tex]\[ g(x) = (x - 3)^4 \][/tex]
### Step 2: Translation 1 Unit Down
Next, we translate the function [tex]\( g(x) = (x - 3)^4 \)[/tex] 1 unit down. To do this, we subtract 1 from the entire function:
[tex]\[ g(x) = (x - 3)^4 - 1 \][/tex]
Thus, the equation that represents the transformation of the parent quartic function [tex]\( f(x) = x^4 \)[/tex] by translating it 3 units to the right and 1 unit down is:
[tex]\[ g(x) = (x - 3)^4 - 1 \][/tex]
### Conclusion
From the given options:
A. [tex]\( g(x) = (x - 3)^4 - 1 \)[/tex]
B. [tex]\( g(x) = (x - 1)^4 + 3 \)[/tex]
C. [tex]\( g(x) = (x + 3)^4 - 1 \)[/tex]
D. [tex]\( g(x) = (x + 1)^4 + 3 \)[/tex]
Option A, [tex]\( g(x)=(x-3)^4-1 \)[/tex], correctly represents the transformation. Therefore, the correct answer is:
[tex]\[ \boxed{A} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.